Traditional Medicinal Practices among the Various Tribal Groups of Kanker District of Bastar Division - Mishra, Dinesh; , Rajesh; Chakravarty, Moyna; Goutam, M. P. (Indian Forester, 2006)
The present study is an attempt to explore the ethno-medicinal system of the tribal and rural areas of the Kanker District, Bastar Division (Chhattisgarh) not as a set of abstract beliefs and practices, in isolation, but as an essential part of the tribal social structure. The study mainly deals with the indigenous herbal mode of treatment among the tribal and rural people of the area. Though modern medical facilities are present in that area but herbal remedies play an important role in their culture. It is an interesting fact that they accept modern medicine, but have ardent faith in herbal medicines and use them for different types of sufferings.